EKTIVITAS KEPEMIMPINAN DAN KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KAUR - Dani, Rahiman; Sofyan, Elpi; Aprianty, Henny; Noviyanto, Hernowo (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This study aims to analyze and see the effectiveness of leadership and employee performance in improving the quality of development planning in Kaur District. The type of research used in this thesis is descriptive qualitative, the data in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is using qualitative data analysis. The results of this study indicate that: the effectiveness of leadership and employee performance in improving the quality of development planning in Kaur Regency has been implemented properly and responsibly, both seen from the aspect of leadership effectiveness which includes: a) Personality, past experience and expectations of leaders, b) Awards and behavior of superiors, c) Characteristics, expectations and behavior of subordinates, d) Task requirements, e) Organizational climate and policies, and f) Expectations and Behavior of colleagues. Then from the aspect of employee performance, which includes: a) Quality of work, b) Quantity, c) Determination of work, d) Effectiveness, and e) Work independence. Employees have also tried to make leadership and employee performance more effective in improving the quality of development planning in Kaur District.